The Effects of Insulin Infusion Protocol on the Glycemic Level of the Intensive Care Patients - Zukhi J.; Suhaimi F.M.; Mazlan M.Z.; Jamaludin U.K.; Razak N.; Sopian M.M. (Elsevier B.V., 2023)
Digital storage; Glucose; Insulin; Critical care; Glycemic control; HUSM; Insulin infusions; Intensive-care patients; Malaysia; Model-based glycemic control; Model-based OPC; Standard protocols; Intensive care units